A pH-reduction dual-responsive shape memory polyurethane composite material, a preparation method and application thereof

CN122790197APending Publication Date: 2026-09-22HIGH & NEW TECH RES CENT OF HENAN ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202611069410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供一种pH-还原双响应的形状记忆聚氨酯复合材料、制备方法及应用,解决传统材料响应单一、生物活性弱、缺乏可视化监测等技术瓶颈

Benefits of technology

同时实现“pH响应-还原响应-热致形状记忆”的三重调控:可响应肿瘤微环境、创面弱酸性环境以及体内高还原环境,相比传统单响应材料,刺激调控方式更多元,适配体内复杂生理环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a pH-reduction dual-response shape memory polyurethane composite material and a preparation method and application thereof, belongs to the technical field of functional shape memory polyurethane materials, and is obtained by co-reaction of a shape memory polyurethane material and curcumin particles; the shape memory polyurethane material is composed of a soft segment and a hard segment, the soft segment is composed of polycaprolactone dihydric alcohol and other polyester / ether dihydric alcohol, and the hard segment is formed by reaction of diisocyanate and a small-molecule chain extender; the small-molecule chain extender comprises curcumin and a Schiff base containing a disulfide bond. In the application, the curcumin is first chemically bonded to a polyurethane main chain, a reduction response site is constructed by combining a disulfide bond, and pH response is performed relying on the intrinsic structure of the curcumin; polycaprolactone crystalline soft segments are matched to realize thermal-induced shape memory; and the hydrogen bond action between the curcumin particles and the polyurethane in blending is utilized to improve the bioavailability; and the fusion of bioactivity, multiple stimulus response and shape memory is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of functionalized shape memory polyurethane materials, specifically to pH-reduction dual-responsive shape memory polyurethane composite materials, their preparation methods, and applications. Background Technology

[0002] Shape memory polyurethane is a typical smart polymer material that achieves its shape memory effect through microphase separation and reversible phase transitions between soft and hard segments in its molecular chain. With its excellent flexibility, processability, and biocompatibility, it is widely used in medical implant materials, wound dressings, and flexible devices. To expand its applications, researchers have introduced functional groups into the polyurethane molecular chain to develop single-stimulus or multi-stimulus responsive shape memory polyurethanes. pH response and redox response are the two most common response modes in the biomedical field. Currently, publicly available pH-reduction dual-responsive shape memory polyurethanes mainly achieve both pH and reduction responses by introducing carboxyl groups, tertiary amines, and disulfide bonds into the polyurethane chain. While these materials exhibit excellent responsiveness, they lack naturally occurring bioactive components and additional functions such as antioxidant, antibacterial, and fluorescence visualization, limiting their application in high-end medical scenarios such as tumor treatment and chronic wound repair.

[0003] Curcumin is a natural polyphenolic active substance with excellent biocompatibility, antioxidant, antibacterial, antitumor and fluorescent properties. The phenolic hydroxyl groups and β-diketones in its molecular structure can naturally endow materials with pH responsiveness. Existing technologies have reported on the composite of curcumin and polyurethane, mainly in two ways. One is to modify polyurethane by physical blending. This method often results in drug-loaded systems such as nanomicelles and microspheres, which are dispersed nanomaterials and cannot be used as independent shape memory bulk materials (CN107625965B, CN105816427A, CN116622045A, CN118403012A). It also often suffers from problems such as easy precipitation and poor stability. The other method is to introduce curcumin into the polyurethane chain by chemical bonding. Although this solves the problems of easy precipitation and poor stability, it only focuses on a single pH response and does not combine with disulfide bonds to build a reduction response system (CN116041654 B, CN116425946A, CN118543817A), nor does it develop bulk shape memory function (CN116622045A, CN110051855A). In summary, no polyurethane bulk material in the current technology integrates four functions: curcumin, pH response, disulfide bond reduction response, and thermo-induced shape memory.

[0004] In existing technologies, curcumin-modified polyurethanes mostly focus on single pH response, without systematic integration with reduction response and bulk shape memory functions. Although there are reports on pH-reduction dual-response shape memory polyurethanes, they generally lack natural bioactive groups (such as curcumin) and have insufficient biocompatibility, antioxidant properties, and fluorescence visualization capabilities. This invention is the first to introduce curcumin chemical bonding into a disulfide bond crosslinked polyurethane network, synergistically constructing a triple functional system of "curcumin pH response—disulfide bond reduction response—PCL thermally induced shape memory," solving the technical bottlenecks of traditional materials such as single response, weak bioactivity, and lack of visual monitoring. It has significant application value in intelligent medical dressings, minimally invasive interventional stents, and controlled drug release systems in complex biological microenvironments. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a pH-reduction dual-response shape memory polyurethane composite material, its preparation method, and its application, solving the technical bottlenecks of traditional materials such as single response, weak bioactivity, and lack of visual monitoring.

[0006] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A pH-reduction dual-responsive shape memory polyurethane composite material is obtained by co-reaction of shape memory polyurethane material and curcumin particles; the shape memory polyurethane material is composed of soft segments and hard segments, the soft segments are composed of polycaprolactone diol and other polyester / ether diols, and the hard segments are formed by reaction of diisocyanate and small molecule chain extender.

[0007] The core design concept is as follows: Matrix design: Polycaprolactone (PCL) is used as the soft segment to provide the reversible crystallization-melting transition required for thermally induced shape memory. Curcumin and Schiff bases containing disulfide bonds are selected to construct the hard segment with isocyanate. The shape memory efficiency and mechanical properties are improved by relying on the microphase separation between the soft and hard segments in polyurethane.

[0008] Reduction-responsive design: Schiff bases containing disulfide bonds are introduced into polyurethane. The disulfide bonds can be specifically recognized and broken by reducing substances such as glutathione (GSH) and dithiothreitol (DTT) in high concentrations in organisms, thereby achieving reduction-triggered network dissociation and shape regulation.

[0009] pH-responsive design: Curcumin is incorporated into the polyurethane chain as a chain extender. By utilizing the protonation / deprotonation behavior of its phenolic hydroxyl groups and β-diketone structure under different pH conditions, the mechanical, morphological, and color changes in acid-base response are achieved.

[0010] Biofunctional design: Curcumin is introduced into polyurethane composite materials through blending. Curcumin particles are released precisely and controllably through a pH-reduction dual response, giving full play to the natural antioxidant, antibacterial and fluorescent properties of curcumin, and endowing the material with additional biological functions and in-situ detection capabilities.

[0011] First, curcumin is chemically bonded to the polyurethane backbone, and disulfide bonds are used to construct reduction response sites, relying on the intrinsic structure of curcumin to achieve pH response. Polycaprolactone crystalline soft segments are then used to achieve thermo-induced shape memory. More importantly, the curcumin particles in the blend bind tightly to the curcumin on the polyurethane backbone through hydrophobic interactions and hydrogen bonding, significantly improving the bioavailability of curcumin. Furthermore, the pH-reduction dual response enables controllable and precise release of curcumin particles, resulting in excellent biological efficacy. This achieves a perfect fusion of bioactivity, multi-stimulus response, and shape memory performance, overcoming the shortcomings of existing materials such as single response function, insufficient bioactivity, limited application forms, and insufficient visual monitoring, thus expanding their application in the biomedical field.

[0012] The polyester / ether diols include, but are not limited to, one or two of polylactide diol, polyglycolic acid diol, polyethylene glycol, polypropylene glycol, poly(γ-butyrolactone) diol, and poly(δ-valerol) diol, all of which have a number-average molecular weight ≤ 8000 g / mol and a molecular weight distribution of less than 1.5.

[0013] The diisocyanate includes, but is not limited to, 4,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate, L - One or both of lysine diisocyanate and isophorone diisocyanate; the small molecule chain extender includes curcumin and Schiff bases containing disulfide bonds.

[0014] The Schiff base containing a disulfide bond is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. The structural formula is shown below:

[0015] The method for preparing the pH-reduction dual-responsive shape memory polyurethane composite material includes the following steps: Step S1: Under a protective atmosphere, place polycaprolactone diol and other polyester / ether diols in a reaction flask to dry and remove water, then heat to above their melting point to fully melt and mix evenly; Step S2: Under a protective atmosphere, diisocyanate is added to molten mixed diols, and after sufficient reaction, an isocyanate-terminated prepolymer is obtained. Step S3: Under a protective atmosphere, Schiff base solution and curcumin solution are added to the system obtained in step 2 in turn, and the reaction is carried out to obtain a dilute polyurethane solution. Step S4: Under a protective atmosphere, add curcumin solution dropwise to the dilute polyurethane solution obtained in step 3, and stir thoroughly to obtain a polyurethane composite material solution. Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in a poor solvent, then redissolved in a good solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film.

[0016] The molar ratio of the diol, diisocyanate, and small molecule chain extender is (0.5-1):(1-4):(0.5-3), and the molar ratio of Schiff base containing disulfide bonds and curcumin in the small molecule chain extender is (0.2-0.9):(1.6-0.2).

[0017] In steps S2 and S3, the reaction temperature is 60–100 °C.

[0018] In steps S3 and S4, the solvents for the curcumin solution and the Schiff base solution are N,N-dimethylformamide, toluene, tetrahydrofuran, or dimethyl sulfoxide. In step S4, the undesirable solvents include, but are not limited to, one or two of methanol, ethanol, n-hexane, ethyl acetate, acetonitrile, etc., and the good solvents include, but are not limited to, one or two of N,N-dimethylformamide, toluene, hexafluoroisopropanol, or dimethyl sulfoxide, etc.

[0019] The aforementioned pH-reduction dual-responsive shape memory polyurethane composite material, which possesses both pH-reduction dual-responsiveness and shape memory function, is applied in food packaging, food indicators, and biomedical implant materials in tumor microenvironments.

[0020] The pH response function is as follows: the polyurethane composite material can produce significant color changes in different pH environments, which can realize the visual monitoring and identification of food spoilage and decay. The reduction responsiveness is as follows: the polyurethane composite material contains disulfide bonds that can be reduced and broken. Under the action of high concentration of glutathione in the tumor microenvironment, the disulfide bonds undergo redox reaction and break, causing the molecular chain of the polyurethane composite material to degrade and break, and rapidly release the curcumin loaded inside. This not only exerts the antibacterial and anti-inflammatory biological effects of curcumin itself, but also greatly improves the drug release rate of the system and effectively inhibits the proliferation of cancer cells. The shape memory function is as follows: when the polyurethane composite material is placed in a hydrothermal environment of 45℃~55℃, its shape fixation rate and shape recovery rate can both reach more than 90%.

[0021] Polyurethane composites have excellent mechanical properties, with a tensile strength of 10–30 MPa and an elongation at break of 1000–2800%, which can meet the application requirements of many occasions.

[0022] Compared with the prior art, the present invention has the following beneficial effects: Simultaneously achieving triple regulation of "pH response - reduction response - thermal shape memory": it can respond to the tumor microenvironment, the weakly acidic environment of the wound, and the highly reducing environment in vivo. Compared with traditional single-response materials, the stimulation regulation mode is more diverse and adaptable to the complex physiological environment in vivo.

[0023] The active components are stable and rich in biological functions: On the one hand, some curcumin is chemically bonded to the polyurethane backbone to solve the problems of easy precipitation and poor stability in physical blending systems, and pH-responsive sites are constructed; on the other hand, hydrophobic and hydrogen bonding are used to tightly bind some curcumin to the polyurethane backbone, which not only improves the bioavailability of curcumin, but also endows the material with functions such as antioxidant, antibacterial, and fluorescence visualization, thereby realizing in-situ monitoring of the material state, which has significant advantages in wound repair and tumor treatment.

[0024] Excellent shape memory performance and adjustable mechanical properties: Relying on the microphase separation between the soft and hard segments of polycaprolactone crystals, the material has a shape fixation rate of ≥90% and a shape recovery rate of ≥90%. The trigger temperature is close to the range of human tolerance. It can be processed into various bulk materials such as films, porous scaffolds, and block elastomers to meet different application needs such as minimally invasive implantation and wound coverage.

[0025] The preparation process is simple and has high industrialization feasibility: the overall synthesis route is a classic stepwise polymerization reaction of polyurethane, the reaction conditions are mild, the raw materials are commercially available, no complex equipment is required, the process has good repeatability, and it has both laboratory research and industrial production value.

[0026] With a wide range of applications, it can be used as intelligent medical wound dressing, tumor local shape memory scaffold, controlled-release drug carrier, tissue engineering scaffold, etc., and has broad development prospects in the field of biomedical intelligent materials. Attached Figure Description

[0027] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0028] Figure 1 The Fourier transform infrared spectra of the polyurethane composite films obtained in Examples 6-8 are shown.

[0029] Figure 2The following are DSC test curves of the polyurethane composite films obtained in Examples 6-8: first heating curve (a); first cooling curve (b); second heating curve (c).

[0030] Figure 3 The static water contact angle test diagrams are for the polyurethane composite membranes obtained in Examples 6-8.

[0031] Figure 4 The mechanical properties test diagrams are for the polyurethane composite films obtained in Examples 6-8.

[0032] Figure 5 The image shows the UV absorption test results of the polyurethane composite membrane solution obtained in Example 6 at different pH values.

[0033] Figure 6 The graph shows the changes in UV absorption after adding different volumes of sodium hydroxide solution to the polyurethane composite membrane solution obtained in Example 6. - Concentration: 0.1 mol / L.

[0034] Figure 7 The graph shows the change in UV absorption over time after adding 110 μL of sodium hydroxide solution to the polyurethane composite membrane solution obtained in Example 6. - Concentration: 0.1 mol / L; Time: min.

[0035] Figure 8 The color changes of the polyurethane composite membrane solution obtained in Example 6 at different pH values ​​are shown in (a); the color changes of the polyurethane solution after adding different equivalent amounts of alkaline solution are shown in (b).

[0036] Figure 9 This is a shape memory test diagram of the polyurethane composite film obtained in Example 6. Detailed Implementation

[0037] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example 1

[0038] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~8000g / mol, 20g) and polylactide diol ( M n~2000 g / mol, 40 g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, 4,4'-diphenylmethane diisocyanate (11.26 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (100 °C) for 2 h to obtain an isocyanate-terminated prepolymer; Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.5 g / ml, 4.1 ml) and a portion of curcumin solution (0.5 g / ml, 13.3 ml) are slowly added dropwise to the system obtained in step 2. The mixture is then reacted in an oil bath (100 °C) for 5 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.5 g / ml, 13.3 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 30 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in methanol, then redissolved in hexafluoroisopropanol solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 2

[0039] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~5000g / mol, 30g) and polyethylene glycol ( M n ~4000 g / mol, 20g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was then placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, gradually add the following to the reaction flask from step 1: L -Lysine diisocyanate (9.95g) was reacted in an oil bath (100℃) for 2 hours to obtain an isocyanate-terminated prepolymer; Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.75 g / ml, 18.1 ml) and a portion of curcumin solution (0.25 g / ml, 4.9 ml) are slowly added dropwise to the system obtained in step 2. The mixture is then reacted in an oil bath (80 °C) for 5 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 4.9 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 25 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in ethanol, then redissolved in toluene solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 3

[0040] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~1000g / mol, 20g) and polypropylene glycol ( M n ~6000 g / mol, 24g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, isophorone diisocyanate (10.67 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (80 °C) for 2 h to obtain an isocyanate-terminated prepolymer. Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (1.0 g / ml, 2.2 ml) and a portion of curcumin solution (0.25 g / ml, 28.3 ml) were slowly added dropwise to the system obtained in step 2. The mixture was reacted thoroughly in an oil bath (60 °C) for 6 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds was obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 28.3 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 35 min to obtain polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in n-hexane, then redissolved in DMF solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 4

[0041] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~3000 g / mol, 36 g) and poly-γ-butyrolactone diol ( M n ~5000 g / mol, 28g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the flask. The flask was dried to remove water, and the reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, isophorone diisocyanate (7.83 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (80 °C) for 2 h to obtain an isocyanate-terminated prepolymer. Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.4 g / ml, 8.0 ml) and a portion of curcumin solution (0.25 g / ml, 15.6 ml) are slowly added dropwise to the prepolymer system obtained in step 2. The mixture is reacted fully in an oil bath (70 °C) for 5 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 15.6 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 10 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in acetonitrile, then redissolved in DMSO solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 5

[0042] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~3000g / mol, 15g) and polyethylene glycol ( M n~2000g / mol, 15g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, 1,6-hexamethylene diisocyanate (6.31 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (90 °C) for 2 h to obtain an isocyanate-terminated prepolymer. Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.25 g / ml, 22.83 ml) and a portion of curcumin solution (0.75 g / ml, 6.14 ml) are slowly added dropwise to the prepolymer system obtained in step 2. The mixture is reacted fully in an oil bath (90 °C) for 5 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 6.14 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 30 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in ethyl acetate, then redissolved in DMF solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 6

[0043] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~3000g / mol, 25g) and polyethylene glycol ( M n ~2000g / mol, 25g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, 1,6-hexamethylene diisocyanate (7.01 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (80 °C) for 2 h to obtain an isocyanate-terminated prepolymer. Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.25 g / ml, 19.0 ml) and a portion of curcumin solution (0.25 g / ml, 15.4 ml) are slowly added dropwise to the system obtained in step 2. The mixture is reacted fully in an oil bath (80 °C) for 6 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 15.4 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 30 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in methanol, then redissolved in DMF solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 7

[0044] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~3000g / mol, 25g) and polyethylene glycol ( M n ~6000g / mol, 25g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the flask. The flask was dried to remove water, and the reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, 1,6-hexamethylene diisocyanate (4.20 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (80 °C) for 2 h to obtain an isocyanate-terminated prepolymer; Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.25 g / ml, 11.5 ml) and a portion of curcumin solution (0.25 g / ml, 9.2 ml) are slowly added dropwise to the system obtained in step 2. The mixture is reacted fully in an oil bath (80 °C) for 6 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 9.2 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 30 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in methanol, then redissolved in DMF solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 8

[0045] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~3000g / mol, 25g) and polyethylene glycol ( M n ~8000g / mol, 25g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was then placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, 1,6-hexamethylene diisocyanate (3.85 g) was gradually added dropwise to the reaction flask in step 1, and the mixture was reacted fully in an oil bath (80 °C) for 2 h to obtain an isocyanate-terminated prepolymer. Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.25 g / ml, 10.5 ml) and a portion of curcumin solution (0.25 g / ml, 8.5 ml) are slowly added dropwise to the system obtained in step 2. The mixture is reacted fully in an oil bath (80 °C) for 6 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 8.5 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 30 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in methanol, then redissolved in DMF solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film. Example 9

[0046] This embodiment provides a method for preparing a pH-reduction dual-responsive shape memory polyurethane composite material, including the following steps: Step S1: Under nitrogen protection, polycaprolactone diol ( M n ~4000 g / mol, 24 g) and polyδ-valerol ( M n~8000g / mol, 32g) were placed in a three-necked flask, and nitrogen gas was passed through and vacuum was drawn repeatedly to replace the gas. The flask was dried to remove water. The reaction flask was placed in a preheated oil bath to allow the two diols to slowly melt and be stirred and mixed evenly. Step S2: Under nitrogen protection, isophorone diisocyanate (4.45 g) is gradually added dropwise to the reaction flask in step 1, and the mixture is reacted fully in an oil bath (100 °C) for 2 h to obtain an isocyanate-terminated prepolymer. Step S3: Under nitrogen protection, a Schiff base solution containing disulfide bonds (0.2 g / ml, 20.5 ml) and a portion of curcumin solution (0.25 g / ml, 1.47 ml) are slowly added dropwise to the system obtained in step 2. The mixture is reacted fully in an oil bath (80 °C) for 6 hours to obtain a dilute polyurethane solution. The Schiff base containing disulfide bonds is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide. Step S4: Under nitrogen protection, add curcumin solution (0.25 g / ml, 1.47 ml) to the dilute polyurethane solution obtained in step 3 again, and mix thoroughly at room temperature for 35 min to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in methanol, then redissolved in DMSO solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film.

[0047] To illustrate the properties of the polyurethane obtained in this invention, the polyurethane material was subjected to the following tests: Fourier Transform Infrared (FTIR), Differential Calorimetry (DSC), Static Tensile Testing, Hardness Testing, and Ultraviolet Absorption Testing. The specific test methods are as follows: Fourier transform infrared spectroscopy (FTIR) was performed using a THERMO FISHE INVENIO FTIR spectrometer at 4000–400 cm⁻¹. -1 The polyurethane material was tested using the ATR reflection mode within the wavenumber range.

[0048] DSC testing: The crystallization and melting behavior of this polyurethane material was tested using a DSC25 instrument from TA Instruments (USA). The test was conducted under a nitrogen atmosphere, with a sample mass of approximately 3-5 mg. The specific test procedure was as follows: First, the sample was heated to 100 °C and held at that temperature for 2 min to eliminate thermal history. Then, it was cooled to -80 °C at a rate of 5 °C / min, and subsequently heated to 100 °C at the same rate.

[0049] Static tensile test: Tensile properties were tested using an electronic universal testing machine (Gotech AI-7000-M) according to the method of GB / T 1040.3-2006, with a tensile rate of 10 mm / min and a room temperature of 25 °C. The mechanical properties were tested using a 200N sensor. At least three polyurethane film samples were tested in parallel for each group, and the average value was taken.

[0050] Shore A hardness test: The hardness of the samples was tested using a Shore A hardness tester (Weido LXD-A) according to the national standard GB / 531-1999 "Rust Pocket Hardness Tester - Indentation Hardness Test Method". The parameters were set as follows: test temperature 25 ℃, each sample was measured in parallel at least 5 times, and the median value was taken as the final test result.

[0051] Static water contact angle test: The water contact angle of the hot-pressed samples was tested using a contact angle measuring instrument (DSA25E) from Krüss GmbH, Germany. The test procedure was set as follows: water contact angle data were recorded starting 3 seconds after a water droplet contacted the polyurethane material surface. The droplet size was 5 μL, and data was collected every 30 seconds for a total of 10 minutes. At least three points were tested on each sample surface, and the average value was taken as the final result.

[0052] Ultraviolet absorption test: The UV-3600 UV-Vis spectrophotometer was used for measurement. The solvent was dimethyl sulfoxide (DMSO). An appropriate amount of polyurethane film sample was weighed and dissolved in DMSO solvent. The UV absorption of the raw material was measured and compared with the UV absorption in different pH environments.

[0053] To illustrate that the polyurethane composite material of the present invention is a pH-reduction dual-responsive shape memory material, the same synthesis steps as in Examples 6-8 were used, but only a Schiff base containing disulfide bonds was used as a chain extender to synthesize Comparative Sample 1, thereby demonstrating the importance of using curcumin as a partial chain extender and blend particles for the pH response characteristics of the polyurethane composite material.

[0054] Figure 1 The Fourier transform infrared spectra of the polyurethane composite films obtained in Examples 6-8 are shown below. The results show that the polyurethane composite films have a high molecular weight distribution in the range of 2250–2270 cm⁻¹. -1 The absence of characteristic peaks for -NCO functional groups at the wavenumber range indicates that all isocyanates participated in the polymerization reaction to form urethane bonds, and no unreacted -NCO groups remained in the reaction system. Furthermore, comparing this spectrum with the infrared spectrum of the raw material, the polyurethane material exhibits better performance at 3500 cm⁻¹. -1The disappearance of the characteristic peak of the terminal -OH at the wavenumber indicates that the raw material diols also participated in the reaction, and no -OH residue remained in the polyurethane material. Although the curcumin involved in the blend has hydroxyl groups in its structure, it is speculated that these hydroxyl groups may not appear in the infrared spectrum because they are involved in hydrogen bonding or are present in small amounts. At 1535 cm⁻¹ -1 The strong, sharp absorption near the wavenumber represents the CN stretching vibration peak in the ethyl carbamate group, commonly referred to as the amide-(I) absorption peak. At 3319 cm⁻¹ -1 The absorption peak at 1626 cm⁻¹ corresponds to the stretching vibration of the NH bond. -1 With 1515 cm -1 The nearby absorption peaks correspond to the stretching vibrations of the aromatic CO and C-C bonds in curcumin, respectively. Although the characteristic absorption peaks of the SS and CS bonds in the infrared spectrum are too weak to be distinguished, they can still be characterized by Raman spectroscopy. These results confirm the successful preparation of the polyurethane material.

[0055] To compare the effect of soft segment chain length on the material's properties, Examples 6-8, using the same synthesis method, varied the chain length of polyethylene glycol. This allowed for the control of the material's basic physicochemical properties, such as mechanical properties, hydrophilicity / hydrophobicity, thermal stability, and crystallinity, making it more suitable for various applications. Figure 2 , 3 Figures 4 and 5 are the DSC, static water contact angle, and mechanical property test results of the polyurethane materials obtained in Examples 6-8, respectively. Figure 2 Table 1 shows the mechanical property data of the polyurethane composite films obtained in Examples 6-8: (a) First heating curve; (b) First cooling curve; (c) Second heating curve. Table 1. Mechanical property data of polyurethane composite films obtained in Examples 6-8.

[0056]

[0057] These test results all demonstrate that the melting temperature of this type of polyurethane is 46~60℃, the mechanical strength is 10~20MPa, and the elongation at break is greater than 2000%, which fully meets the requirements for use and processing in food packaging, food preservation, and biomedical implant devices.

[0058] Figure 5-8 The response changes of polyurethane composites under different pH environments are shown, among which, Figure 8 Figure a shows the color change of the polyurethane composite solution at different pH values. Figure 8 b is a graph showing the color changes after adding different equivalent amounts of alkaline solution to the polyurethane solution.

[0059] Depend on Figure 8 and Figure 5It is evident that the color of the polyurethane solution changes significantly under different pH conditions, gradually transforming from a yellowish-green solution to an orange-yellow solution. Furthermore, this change is observed when an alkaline solution (such as sodium hydroxide solution) is added. Figure 6 ), add 10-200 μL of OH to the material solution sequentially. - It was found that the absorption peak of this material at 422.0 nm gradually decreased, and a new absorption peak appeared at 623.0 nm. However, with the addition of more alkaline solution, the absorption peak gradually decreased until the absorption at 623 nm completely disappeared. A new absorption peak appeared at 498.0 nm, and with the addition of more alkaline solution, the absorption peak at 498.0 nm gradually increased. The color of the polyurethane solution also changed from yellow-green to orange. This is because when a small amount of alkaline solution is added, the hydroxyl groups on the enol form of curcumin in the polyurethane composite material preferentially dissociate to form oxygen anions. As more alkaline solution is added, the hydroxyl groups (OH-) dissociate. - The more (the more), the more active hydrogen atoms on curcumin gradually dissociate to form oxygen anions, increasing the maximum absorption wavelength and absorbance, until the added OH... - With sufficient amounts of curcumin, the enol hydroxyl groups and double-bonded hydrogens in the curcumin are completely dissociated, at which point the maximum absorption wavelength and absorbance of the polyurethane solution reach their maximum. It was also found that the polyurethane solution after the addition of alkaline solution is unstable; the solution color gradually lightens within 45 minutes, and the absorption wavelength also changes accordingly. Figure 7 This originates from the reversible enol-keto tautomerism in curcumin.

[0060] The shape memory behavior of this type of thin film under thermal response was studied in detail using the three-point bending method. Figure 9 As shown, a polyurethane composite film was heated in a 45°C oven for 3 minutes, folded, and fixed at room temperature for 3 minutes. The shape fixation rate after folding was 91.12%. Upon re-entry into the 45°C oven, the sample recovered its original shape within 3 minutes, achieving a shape recovery rate of 92.35%. Following the same method, the polyurethane material was heated in a 50°C oven for 1 minute, folded, and fixed at room temperature for 1 minute. The shape fixation rate after folding was 97.86%. Upon re-entry into the 50°C oven, the sample recovered its original shape within 1 minute, achieving a shape recovery rate of 98.24%. Similarly, at 55°C, the shape fixation and recovery experiments showed that the sample could fix and recover its shape in a shorter time, with both fixation and shape recovery rates reaching 98%. However, if the oven temperature was adjusted to 60°C or higher, the sample quickly melted and deformed. Although it could recover its shape under heat stimulation, the deformation of the material affected and limited its application.

[0061] The pH-reduction dual-responsive curcumin-based shape memory polyurethane material obtained in this invention combines the excellent processability and mechanical properties of polyurethane, the bioactivity and fluorescence characteristics of curcumin, and the dual stimulus-response capability brought by disulfide bonds and the curcumin structure, filling the technological gap in the intersection of curcumin-modified polyurethane and pH-reduction dual-responsive shape memory polyurethane. This type of material is flexible in form, has good biocompatibility, and multiple controllable responses. Its main applications include: intelligent responsive medical dressings for chronic and infected wounds; shape memory implant scaffolds and locally controlled drug release systems for minimally invasive tumor intervention; porous scaffolds for soft tissue repair; and intelligent flexible materials for in vitro biological microenvironment simulation and fluorescence visualization.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A pH-reduction dual-responsive shape memory polyurethane composite material, characterized in that, It is obtained by co-reaction of shape memory polyurethane material and curcumin particles; the shape memory polyurethane material is composed of soft segments and hard segments, the soft segments are composed of polycaprolactone diol and other polyester / ether diols, and the hard segments are formed by reaction of diisocyanate and small molecule chain extender.

2. The pH-reduction dual-responsive shape memory polyurethane composite material according to claim 1, characterized in that, The polyester / ether diols include, but are not limited to, one or two of polylactide diol, polyglycolic acid diol, polyethylene glycol, polypropylene glycol, poly(γ-butyrolactone) diol, and poly(δ-valerol) diol, with a number-average molecular weight ≤8000 g / mol and a molecular weight distribution of less than 1.

5.

3. The pH-reduction dual-responsive shape memory polyurethane composite material according to claim 1, characterized in that, The diisocyanates include, but are not limited to, 4,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate, L - One or both of lysine diisocyanate and isophorone diisocyanate; the small molecule chain extender includes curcumin and Schiff bases containing disulfide bonds.

4. The pH-reduction dual-responsive shape memory polyurethane composite material according to claim 3, characterized in that, The Schiff base containing a disulfide bond is obtained by reacting p-hydroxybenzaldehyde with 4,4'-diaminodiphenyl disulfide.

5. The method for preparing the pH-reduction dual-responsive shape memory polyurethane composite material according to any one of claims 1-4, characterized in that, Includes the following steps: Step S1: Under a protective atmosphere, place polycaprolactone diol and other polyester / ether diols in a reaction flask to dry and remove water, then heat to above their melting point to fully melt and mix evenly; Step S2: Under a protective atmosphere, diisocyanate is added to molten mixed diols, and after sufficient reaction, an isocyanate-terminated prepolymer is obtained. Step S3: Under a protective atmosphere, Schiff base solution and curcumin solution are added to the system obtained in step 2 in turn, and the reaction is carried out to obtain a dilute polyurethane solution. Step S4: Under a protective atmosphere, add curcumin solution dropwise to the dilute polyurethane solution obtained in step 3, and stir thoroughly to obtain a polyurethane composite material solution; Step S5: The polyurethane composite material solution obtained in step 4 is precipitated and washed in a poor solvent, then redissolved in a good solvent, poured into a polytetrafluoroethylene mold, and the solvent is evaporated while hot to obtain a polyurethane composite film.

6. The method for preparing the pH-reduction dual-responsive shape memory polyurethane composite material according to claim 5, characterized in that, The molar ratio of the diol, diisocyanate, and small molecule chain extender is (0.5-1):(1-4):(0.5-3), and the molar ratio of Schiff base containing disulfide bonds and curcumin in the small molecule chain extender is (0.2-0.9):(1.6-0.2).

7. The method for preparing the pH-reduction dual-responsive shape memory polyurethane composite material according to claim 5, characterized in that, In steps S3 and S4, the solvents for the curcumin solution and the Schiff base solution are N,N-dimethylformamide, toluene, tetrahydrofuran, or dimethyl sulfoxide.

8. The method for preparing the pH-reduction dual-responsive shape memory polyurethane composite material according to claim 5, characterized in that, In step S4, undesirable solvents include, but are not limited to, one or two of methanol, ethanol, n-hexane, ethyl acetate, acetonitrile, etc., while good solvents include, but are not limited to, one or two of N,N-dimethylformamide, toluene, hexafluoroisopropanol, or dimethyl sulfoxide, etc.

9. The application of the pH-reduction dual-responsive shape memory polyurethane composite material according to any one of claims 1-4, characterized in that, The polyurethane composite material has a dual pH-reduction response function and also has shape memory function, and can be applied to food packaging, food indicators, and biomedical implant materials in tumor microenvironments.

10. The application of the pH-reduction dual-responsive shape memory polyurethane composite material according to claim 9, characterized in that: The pH response function is as follows: the polyurethane composite material can produce significant color changes in different pH environments, which can realize the visual monitoring and identification of food spoilage and decay. The reduction responsiveness is as follows: the polyurethane composite material contains disulfide bonds that can be reduced and broken. Under the action of high concentration of glutathione in the tumor microenvironment, the disulfide bonds undergo redox reaction and break, causing the molecular chain of the polyurethane composite material to degrade and break, and rapidly release the curcumin loaded inside. This not only exerts the antibacterial and anti-inflammatory biological effects of curcumin itself, but also greatly improves the drug release rate of the system and effectively inhibits the proliferation of cancer cells. The shape memory function is as follows: when the polyurethane composite material is placed in a hydrothermal environment of 45℃~55℃, its shape fixation rate and shape recovery rate can both reach more than 90%.

Citation Information

Patent Citations

  • Curcumin micelle drug-loaded system and preparation method thereof

    CN105816427A

  • Nanomedicine carrier, drug delivery system containing the nanomedicine carrier, and method for preparing the drug delivery system.

    CN107625965B

  • Preparation method and application of poly-curcumin prodrug nanocarrier with reactive oxygen responsiveness high drug loading capacity

    CN110051855A

  • An absorbable pancreatic drainage tube capable of adaptive fitting, antibacterial and anti-inflammatory and a preparation method thereof

    CN116041654B

  • Curcumin-based polyurethane material as well as preparation method and application thereof

    CN116425946A